Alcohol and pregnancy - Anna Maria Paoletti; Ileana Atzeni; Marisa Orrù; Monica Pilloni; Alessandro Loddo; Martina Zirone; Maria Francesca Marotto; Pierina Zedda; Maria Francesca Fais; Emanuela Stochino Loi; Graziella Boi; Gian Benedetto Melis (Hygeia Press di Corridori Marinella, 2013)
Alcohol exerts teratogenic effects in all the gestation times, with peculiar features in relationship to the trimester of pregnancy in which alcohol is assumed. Alcohol itself and its metabolites modify DNA synthesis, cellular division, cellular migration and the fetal development. The characteristic facies of feto-alcoholic syndrome (FAS)-affected baby depends on the alcohol impact on skull facial development during the first trimester of pregnancy. In association there are cerebral damages with a strong defect of brain development up to the life incompatibility. Serious consequences on fetal health also depends on dangerous effects of alcohol exposure in the organogenesis of the heart, the bone, the kidney, sensorial organs, et al. It has been demonstrated that maternal binge drinking is a high factor risk of mental retardation and of delinquent behaviour. Unfortunately, a lower alcohol intake also exerts deleterious effects on fetal health. In several countries of the world there is a high alcohol use, and this habit is increased in the women. Therefore, correct information has to be given to avoid alcohol use by women in the preconceptional time and during the pregnancy. Preliminary results of a study performed by the authors show that over 80% of pregnant and puerperal women are not unaware that more than 2 glasses of alcohol/week ingested during pregnancy can create neurological abnormalities in the fetus. However, after the information provided on alcoholic fetopathy, all women are conscious of the damage caused by the use of alcohol to the fetus during pregnancy. This study confirms the need to provide detailed information on the negative effects of alcohol on fetal health.   Proceedings of the 9th International Workshop on Neonatology · Cagliari (Italy) · October 23rd-26th, 2013 · Learned lessons, changing practice and cutting-edge research